El texto instructivo como recurso para el aprendizaje de las funciones verbales - Ortiz Valverde, Jhany Deysi (2022)
This paper aims to support the development of a learning session aimed at improving competence "Write different types of texts in your mother tongue". The session, entitled "Instructional text as a resource for verb domain", seeks to contribute to the solution of the educational problem, in terms of written expression and within the framework established by the National Basic Education Curriculum (CNEB) for regular basic education. The writing or production of texts is a process intended for the student to communicate, through written language, his knowledge, ideals, aspirations or any other manifestation of his own personality, for the purpose not only of expressing oneself but of interacting with its environment, using resources such as writing, which becomes the channel through which all the information to be communicated will circulate, with regard to subjects which are of primary importance from both the pedagogical and practical points of view and which, at the same time, allow the recording of messages which transcend time and space, which can be decoded at any time in history and anywhere in the universe. In this specific case it is considered the elaboration of an instructive text, a recipe, the same that can be put into practice and demonstrate the usefulness of its use in some of the most essential activities of daily life. Similarly, the importance of the verb is established as an indicator of the actions that anyone can perform and as a central element in the construction of the written message and, therefore, adapt the text to the communicative situation; organize and develop ideas in a coherent and cohesive manner; use written language conventions in a relevant manner; reflect and evaluate the form, content and context of the written text.